The Effect of Fiber Laser Parameters on Microhardness and Microstructure of Duplex Stainless Steel - Mohammed, Ghusoon R.; M., Ishak; S. N., Aqida; Hassan, A. Abdulhadi (EDP Sciences, 2016)
An investigation was implement to study the influence of laser power, and speed of the welding on hardness, microstructure, and penetration of laser welding bead on plate duplex stainless steel, which is not exhibited so far. A fiber laser was selected for welding duplex stainless steel sheet with 2 mm thickness. Then, optical microscope (OM) was used in the morphologic observation of cross section, penetration depth, and bead width. Microhardness of the welded sheet was measured using Vickers hardness. Profiles of hardness and microstructure were utilized to discriminate welding line and to propose superior welding parameters. The experimental results displayed that, a good quality of duplex steel welds can be acquired when a suitable fiber laser welding parameters were selected. It was found that microhardness profiles showed a rise in the hardness of the weld and heat-affected zones as the solidification process proceeds rapidly. Additionally, the crystal solidification process induced by the fiber laser welding was schematically clarified and systematically exposed.